Alzheimer's Disease Patients, Especially ApoE4 Carriers, Have Significantly Reduced High‐density Lipoprotein Particle Size Revealed by Negative‐stained Transmission Electron Microscopy. (20th December 2022) - Zheng, Jack Jingyuan; Hong, Brian V.; Agus, Joanne; Guo, Fei; Lebrilla, Carlito B.; Jin, Lee‐Way; Maezawa, Izumi; Harvey, Danielle J.; Zivkovic, Angela M.
Abstract: Background: High density lipoproteins (HDL) are protective against a wide array of diseases and have recently also been found to be associated with reduced risk of Alzheimer's Disease (AD). However, the amount of circulating HDL‐cholesterol does not correlate closely with function, explaining only about 40% of the variance in HDL's ability to perform its primary role of cholesterol efflux. HDL particle composition, size and structure are important determinants of functional capacity, however little is known about HDL particle physical characteristics in AD patients, in particular whether there are apolipoprotein E (APOE) genotype‐dependent effects. Method: Plasma samples from a total of 172 APOE genotyped patients, n = 37 ApoE3/E3 and n = 34 ApoE3/E4 with diagnosed AD, n = 22 ApoE3/E3 and n = 18 ApoE3/E4 with diagnosed MCI, and n = 44 ApoE/E3 and n = 39 ApoE3/E4 age‐ and sex‐matched non‐AD controls were obtained from the UC Davis Alzheimer's Disease Research Center biobank. HDL particles were isolated from plasma by sequential density‐adjusted ultracentrifugation followed by size‐exclusion chromatography. The size of HDL from each patient was characterized using negative‐stained transmission electron microscopy (NS‐TEM) followed by computational particle size analysis. Result: On average, 34 TEM micrographs were obtained, and over 33, 000 individual particles were selected and analyzed from each HDL sample using pre‐determined image quality and image selection criteria. The average particle size were compared between AD patients and controls stratified by APOE genotype. The mean particle diameter of HDL from MCI and AD patients was smaller compared to the control group (8.28 +/‐ 0.587, 8.30 +/‐ 0.662 vs. 8.84 +/‐ 0.587, respectively). The differences remained statistically significant when stratified by genotype. Both MCI and AD group had smaller HDL particle size compared to the control group in the ApoE3/E3 genotype (8.37 +/‐ 0.452, 8.48 +/‐ 0.613 vs. 8.90 +/‐ 0.602, respectively), and in the ApoE3/E4 genotype (8.17 +/‐ 0.707, 8.11 +/‐ 0.667 vs. 8.80 +/‐ 0.582, respectively). Conclusion: These results reveal that patients with Alzheimer's dementia and mild cognitive impairment have disrupted HDL particle distribution, with smaller average HDL particle size, highlighting the need for further studies of lipoprotein metabolism in AD.